PENGARUH BERKUMUR REBUSAN DAUN MINT (Mentha Piperita)TERHADAP PERUBAHAN PH SALIVA - Ika Meylia; Hermin Rimbyastuti (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2014)
Title Influence of gargle with mint (Mentha piperita) leaf water stew to pH saliva alteration Abstract Mint (Mentha Piperita) oil contains menthol which cause cold spicy flavor. Sensation can affect the degree of acidity of saliva (pH). The degree of acidity or down low salivary reach critical pHcan lead to demineralization of the tooth causing caries process. The research objective was to determine the effect of mint leaves boiled water rinse to changes in the pHof saliva. The research used a quasi experiment. The design of this study used a pretest and posttest with control group, the observation was done 2 times before and after treatment. Data analysis method used descriptive quantitative. The study was conducted in class V SDN Asinan Bawen Semarang as many as 26 children were divided into 2 groups, 13 children mint leaves boiled water gargle and rinse with distilled water 13 children. Normality test data by the Kolmogorov-Smirnov. The results of the normality of the data showed p 0.05, which means that the data are normally distributed. The data obtained were analyzed using statistical tests pair t-test and independent T test. The results indicate that there was a description of salivary pHchanges after gargling decoction of the leaves of mint. But statistics show no effect of mint leaves boiled water rinse to changes in saliva pH.From the research results can be recommended to conduct research with material extraction method that does not damage the active substance of the material.